2022
DOI: 10.1002/ppul.26078
|View full text |Cite
|
Sign up to set email alerts
|

Elexacaftor–Tezacaftor–Ivacaftor improves exercise capacity in adolescents with cystic fibrosis

Abstract: Methods: Three adolescents (14.0 ± 1.4 years) with CF (FEV 1 % predicted: 62.5 ± 17.1; F508del/F508del genotype) completed an exhaustive maximal cardiopulmonary exercise test on a cycle ergometer to determine peak oxygen uptake ( VO 2peak ) and measure changes in gas exchange and ventilation during exercise at 6 weeks. We also analyzed wrist-worn device-based physical activity (PA) data in two of the three cases. Validated acceleration thresholds were used to quantify time spent in each PA intensity category.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…A recent study involving nine CF adults with severe lung disease showed improvement in respiratory muscle strength and improved exercise capacity assessed by the 6-minute walk test following Kaftrio treatment [ 31 ]. A study from C auser et al [ 22 ] showed improvements in peak V ′ O 2 , maximal workload and the anaerobic threshold with 6 weeks of Kaftrio treatment. R ysgaard et al [ 23 ] performed a study involving 91 CF patients 12 years of age and older who were started on Orkambi and Symkevi, and showed significant improvements in peak V ′ O 2 and maximal workload on CPET after 1 year of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study involving nine CF adults with severe lung disease showed improvement in respiratory muscle strength and improved exercise capacity assessed by the 6-minute walk test following Kaftrio treatment [ 31 ]. A study from C auser et al [ 22 ] showed improvements in peak V ′ O 2 , maximal workload and the anaerobic threshold with 6 weeks of Kaftrio treatment. R ysgaard et al [ 23 ] performed a study involving 91 CF patients 12 years of age and older who were started on Orkambi and Symkevi, and showed significant improvements in peak V ′ O 2 and maximal workload on CPET after 1 year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is however limited evidence of the impact of CFTR modulators on exercise capacity in CF children. A recent study of three CF adolescents on Kaftrio showed improvement in peak oxygen uptake ( V ′ O 2 ) after 6 weeks of Kaftrio treatment [ 22 ]. A recent Danish study involving 91 patients showed statistically significant improvement in peak V ′ O 2 and maximal workload on CPET 12 months after initiation of treatment with Orkambi or Symkevi [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when pwCF are started on HEMT therapy they tend to have increased forced expiratory ventilation in 1 s (FEV 1 ) and there is evidence that they have an increased exercise capacity ( 7 , 68 ). This relationship is important in considering other factors that may impact pwCF ability to maintain a healthy weight.…”
Section: Obesitymentioning
confidence: 99%
“…Previous studies have reported the potential effects of CFTR modulators in improving physical activity and exercise tolerance [ 83 , 84 , 85 ]. Causer and collaborators assessed whether ETI therapy could improve these parameters in three adolescents with CF after six weeks of the start of the therapy [ 71 ]. They were homozygous for F508del-CFTR and presented moderate to advanced lung disease before the start of ETI therapy.…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%
“…They were homozygous for F508del-CFTR and presented moderate to advanced lung disease before the start of ETI therapy. After the 6-week follow-up, the three participants exhibited an improved peak of the volume of oxygen and exercise capacity, suggesting that ETI therapy might have enhanced the efficiency of respiratory and peripheral muscles [ 71 ]. With a similar aim, Giallongo and collaborators assessed cardiorespiratory polygraph parameters and respiratory muscle strength during sleep in nine PwCF before and 12 months after ETI therapy [ 78 ].…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%